Design and testing of an adhesively bonded CFRP strengthening system for steel structures. (15th December 2018) - Chataigner, S.; Benzarti, K.; Foret, G.; Caron, J.F.; Gemignani, G.; Brugiolo, M.; Calderon, I.; Piñero, I.; Birtel, V.; Lehmann, F.
Highlights: An adhesively bonded CFRP system was developed. This system consists of a UHM CFRP plate and a hybrid epoxy/polyurethane adhesive. Characterizations on the adhesive proved that a post-cure treatment was necessary. A test plan on bonded assemblies was done to assess performance and durability. Abstract: In the framework of sustainable development policies, it is essential that infrastructure owners can rely on effective repair or strengthening solutions, designed and tested in relevance to actual service conditions. In the case of steel structures, fatigue damage is a major concern that can significantly affect the lifespan of the structure, and so far, there are very few operational methods capable of preventing fatigue cracks in the field. Adhesively bonded carbon fiber reinforced polymer (CFRP) composites are being successfully applied to the rehabilitation of concrete structures for more than two decades, and they are currently receiving much interest for the strengthening of steel elements, but mainly for curative purpose after severe damage has occurred. In the present study, which is part of a European project called FASSTbridge, a specific CFRP system has been developed as a preventive method against fatigue damage of steel structures. The proposed system consists of a commercially available ultra-high modulus (UHM) CFRP composite plate compatible with the stiffness of the host steel structures, which is bonded to the steel support using a novel hybrid epoxy/polyurethane adhesive. A first part of the paper presents the main specifications that should be adopted in the design of CFRP strengthening systems applied to steel structures, and that were identified from an extensive literature survey. These specifications have guided the development of the polymer adhesive and the choice of a peculiar commercial CFRP plate in the preliminary phase of the project. Experimental characterizations were then conducted (i) on the formulated hybrid polymer adhesive to optimize its curing schedule and check the previous specifications are fulfilled, and (ii) on CFRP reinforced steel specimens in order to verify the effectiveness of the proposed strengthening system. This experimental program involved both short term and durability tests that were performed by different laboratories. Such an inter-laboratory study made it possible to verify the performances of the developed strengthening system and to assess the influence of installation parameters and environmental conditions.